Complete mitochondrial genome of the oriental armyworm Mythimna separata (Walker) (Lepidoptera: Noctuidae). (2nd November 2015) - Li, Feng-Bo; Wang, Wei; Zhang, Hui-Xian; Shen, Wei-Feng; Xu, Xiao-Yan; Chen, Jin-E; Meng, Zhi-Qi
Abstract: We determined the complete mitochondrial genome of the oriental armyworm Mythimna separata (Walker) (Lepidoptera: Noctuidae), which is one of the serious cereal pests in Asia and Australia. The circular genome of 15, 332 bp in length contains 37 typical animal mitochondrial genes and a non-coding A + T-rich region. Its gene content and order are typical of lepidopteran mitochondrial genomes described to date. All protein-coding genes (PCGs) start with an ATN codon except for cox1 and nad1, which use CGA and TTG as their start codon, respectively. Ten PCGs use complete stop codon TAA, whereas three PCGs end with single T. The A + T-region is located between rrnS and trnM with a length of 374 bp. The mitochondrial genome sequence benefits future studies of molecular phylogenetics and pest control.